2008
DOI: 10.1017/s1368980007000304
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences for front-of-pack calories labelling

Abstract: ObjectiveIn light of the emerging obesity pandemic, front-of-pack calories labels may be an important tool to assist consumers in making informed healthier food choices. However, there is little prior research to guide key decisions on whether caloric content should be expressed in absolute terms or relative to recommended daily intake, whether it should be expressed in per serving or per 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
119
2
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 17 publications
5
119
2
5
Order By: Relevance
“…One reason for a high number of labels could be found in binary standards: There is a low level of differentiation which leads companies and stakeholders to introduce an additional label for their purpose. This supports the argument that consumers are confronted with an information overload (Kolodinsky, 2012;Kroeber-Riel & Esch, 2004;van Kleef et al, 2008). These tendencies and results of consumer research lead to further developments in food labelling, which are explained below.…”
Section: Different Types Of Labellingsupporting
confidence: 62%
“…One reason for a high number of labels could be found in binary standards: There is a low level of differentiation which leads companies and stakeholders to introduce an additional label for their purpose. This supports the argument that consumers are confronted with an information overload (Kolodinsky, 2012;Kroeber-Riel & Esch, 2004;van Kleef et al, 2008). These tendencies and results of consumer research lead to further developments in food labelling, which are explained below.…”
Section: Different Types Of Labellingsupporting
confidence: 62%
“…23 They also show that people have limited knowledge of dietary fats 24 and that although participants are familiar with the notion of calories, they do not always understand how to apply it. 25 As outlined earlier, this study aimed to develop campaigns and associated point-of-choice prompts to influence food choice in workplace cafeterias. Formative focus groups explored employees' interpretations of healthy eating, their knowledge of different labeling strategies, nutrition information, factors affecting food choice at work, and the best way to prompt changes in behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Different nutrition labelling formats have been shown to influence food product healthfulness evaluations, [1][2][3][4][5] however, the experimental design and focus of analysis has generally been on the energy and nutrition content of the labels. So far, the role of reference amounts, an intrinsic element of many of the FoP labelling schemes, appears not to have been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Research since 2005 has shown that consumer confusion related to portion information is still an issue. 11,12 For example, when comparing eight executions of FoP calorie flags, Van Kleef et al 5 reported that consumers found the 'calories per serving flag' option to be most preferable but only under the condition that the portion was perceived to represent a realistic and easy-to-understand consumption unit. There is on-going debate as to whether nutrition information is best presented 'per 100 g/100 ml' or 'per portion' 8,13,14 particularly amongst those concerned with the development of nutrient profiling models which attempt to define 'healthy' versus 'unhealthy' foods.…”
Section: Introductionmentioning
confidence: 99%